Mapping a Decade of Research in BEMS Reports (ISSN: 2454-6895), 2015–2024: A Bibliometric Perspective - Mondal, Debdas (Information Research Communications, 2025)
This study provides a comprehensive bibliometric assessment of BEMS Reports over ten years (2015–2024), examining publication trends, authorship patterns, citation performance, thematic evolution, and advanced impact indicators. A total of 131 publications and 342 citations were analysed using standard and advanced bibliometric measures, including the h-index, g-index, e-index, Age-Weighted Citation Rate (AWCR), AW-index, and coverage metrics. The findings reveal consistent annual growth in research output, with notable increases in collaborative authorship and a strong representation of interdisciplinary subjects such as pharmacology, toxicology, molecular biology, and regenerative medicine. Advanced citation metrics-such as an AWCR of 113.31, AW-index of 10.64, and high h- and g-coverage values-underscore the journal’s expanding research visibility and influence. Institutional contributions from Ireland, India, Nigeria, and Iran further highlight its global reach. Overall, the study demonstrates that BEMS Reports has developed into a significant platform for biomedical and life science research. By systematically mapping its scholarly output, this bibliometric perspective offers valuable insights into the journal’s growth trajectory and reinforces its emerging role within the international scientific community.
Keywords: BEMS Reports; Bibliometric analysis; Citation metrics; AWCR; Authorship patterns; Research productivity; Subject mapping; Scholarly impact; Publication trends; Coverage indicators.